Minat Masyarakat Terhadap KPRS (Kredit pemilikan Rumah Syariah) Dengan Skema Murabahah Pada BNI Syariah KC Surabaya - Suharto, Aisyiatus Shahiyah; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2018)
KPRS (Sharia House Ownership Credit) is one of the superior products of BNI Syariah because it is perceived that the demand for the product will increase from year to year, as well as the biggest revenue earned by BNI Syariah is dominated by murabahah contract which majority comes from KPRS financing. This research uses descriptive qualitative method with aim to know how big of interest of society to KPRS along with the reason, result of research which is got that interest of society to use product of KPRS with murabahah contract increase every year with some underlying motive, one of them because of installment which is fixed and no administrative costs.